1987
DOI: 10.3382/ps.0661489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein and Energy Intake of Broiler Breeder Hens on Performance of Broiler Chicken Offspring

Abstract: Two hundred and forty individually caged Hubbard x Hubbard broiler breeders (BB) were fed one of six diets at 150 g/bird per day, which provided 19 or 25 g protein and 325, 385, or 450 kcal nitrogen-corrected metabolizable energy. In Trial 1, chicks hatched from 29-wk-old BB were sexed and 12 females and 12 males placed in each of four replicate floor pens per treatment. A 23% crude protein (CP) starter (0 to 20 day), 20% CP grower (21 to 34 day) and 18% CP finisher (35 to 41 day) diets were fed. Protein intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
4

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 7 publications
1
4
0
4
Order By: Relevance
“…Wilson and Harms (1984) found that protein intake of 19.9 to 23 g per bird per d had no effect on 49-d body weight of offspring. Similar results were observed by Spratt and Leeson (1987) and Pearson and Herron (1981) using comparable protein intakes.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Wilson and Harms (1984) found that protein intake of 19.9 to 23 g per bird per d had no effect on 49-d body weight of offspring. Similar results were observed by Spratt and Leeson (1987) and Pearson and Herron (1981) using comparable protein intakes.…”
Section: Introductionsupporting
confidence: 93%
“…However, only a few studies have associated the effect of breeder diet with offspring performance (Aitken et al, 1969;Pearson and Herron, 1981;Wilson and Harms, 1984;Spratt and Leeson, 1987). Aitken et al (1969) reported that broilers from parents fed a nutrient-dense diet (energy and protein) were significantly heavier at hatch and at 63 d in comparison with chicks from broiler breeders fed lowenergy diets.…”
Section: Introductionmentioning
confidence: 98%
“…Os resultados obtidos no presente trabalho estão de acordo com Waldroup et al (1976), Pearson & Herron (1981), Spratt & Leeson (1987), segundo os quais o fornecimento de 18 a 20 g/dia parece atender as necessidades dos aminoácidos essenciais, porém níveis mais elevados (23 g/dia) podem ser necessários durante o período de alta produtividade para obtenção de máximo crescimento da massa do ovo.…”
Section: Resultsunclassified
“…As exigências de proteína para matrizes pesadas na fase de produção variam de 18g a 23g/ave/dia (Waldroup et al, 1976;Bornstein et al, 1979;Pearson & Herron, 1981Wilson & Harms, 1984;Spratt & Leeson, 1987;Couto, 1988;Scholoffel et al, 1988;NRC, 1994;Lopez & Leeson, 1995a). Na prática, as recomendações de proteína para reprodutoras pesadas são relativamente altas, recomendando-se formular rações com 16% de proteína bruta, levando uma ave no pico de postura a consumir em torno de 26 g de proteína/dia (Lopez & Leeson, 1995a).…”
Section: Introductionunclassified
“…Ce management a engendré des pertes économiques non négligeables du fait d'une réduction de la masse corporelle des animaux et d'une diminution de leur efficacité alimentaire. Spratt et Leeson (1987) ont aussi montré des différences de dépôt protéique et d'adiposité des carcasses sur des animaux issus de poules reproductrices nourries avec des régimes différant de par leur teneur en énergie et en protéines.…”
Section: Modifications Du Phénotype De Poussins Suite à Des Pratiquesunclassified